The potential synergism by combining external counterpulsation with intermittent theta burst stimulation in post-stroke motor function recovery. (August 2016) - He, Weijia; Au-Yeung, Suk-yin Stephanie; Mak, Margaret; Leung, Thomas Wai Hong; Leung, Howan; Wong, Lawrence Ka Sing
Abstract: Upper limb weakness and incoordination is a common disability following ischemic stroke. Previous studies have showed that the single application of external counterpulsation (ECP) and intermittent theta burst stimulation (iTBS) can effectively enhance the cortical motor excitability and facilitate recovery. However, it remains uncertain if sequential application of these therapies would further augment the recovery. We hypothesize a synergistic effect of ECP followed by iTBS to upper limb function may happen through improvements in both cerebral perfusion and neuron excitability.